Brain plasticity-based therapeutics - Merzenich, Michael M.; Van Vleet, Thomas M.; Nahum, Mor (Frontiers in Human Neuroscience, 2014)
The primary objective of this review article is to summarize how the neuroscience of brain plasticity, exploiting new findings in fundamental, integrative and cognitive neuroscience, is changing the therapeutic landscape for professional communities addressing brain-based disorders and disease. After considering the neurological bases of training-driven neuroplasticity, we shall describe how this neuroscience-guided perspective distinguishes this new approach from a) the more-behavioral, traditional clinical strategies of professional therapy practitioners, and b) an even more widely applied pharmaceutical treatment model for neurological and psychiatric treatment domains. With that background, we shall argue that neuroplasticity-based treatments will be an important part of future best-treatment practices in neurological and psychiatric medicine.